The Second Convict Age: Explaining the Return of Mass Imprisonment in Australia - Andrew Leigh (Center for Economic Studies and ifo Institute (CESifo), 2020)
Constructing a new series of incarceration rates from 1860 to 2018, I find that Australia now incarcerates a greater share of the adult population than at any point since the late nineteenth century. Much of this increase has occurred since the mid-1980s. Since 1985, the Australian incarceration rate has risen by 130 percent, and now stands at 0.22 percent of adults (221 prisoners per 100,000 adults). Recalculating Indigenous incarceration rates so that they are comparable over a long time span, I find that incarceration rates for Indigenous Australians have risen dramatically. Fully 2.5 percent of Indigenous adults are incarcerated (2481 prisoners per 100,000 adults), a higher share than among African-Americans. The recent increase in the Australian prison population does not seem to be due to crime rates, which have mostly declined over the past generation. Instead, higher reporting rates, stricter policing practices, tougher sentencing laws, and more stringent bail laws appear to be the main drivers of Australia's growing prison population.
Keywords: I30; K14; N30; 330; prison; jail; incarceration; crime